2015
DOI: 10.1590/1983-084x/13_074
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of Casearia sylvestris Sw exhibitsin vitro antioxidant and antimicrobial activities andin vivo hypolipidemic effect in rats

Abstract: ABSTRACT:The Casearia sylvestris Sw (Flacourtiaceae) is a shrub that occurs in forests of Southern Brazil; its leaves are widely used in folk medicine as a depurative, analgesic, anti-inflammatory and antiulcerogenic agent. The objective of this study was to perform the phytochemical description and to evaluate the pharmacological activities (antimicrobial, antifungal, antioxidant and toxicity) of the ethanolic extract (EE) of C. sylvestris Sw. In addition, we also evaluated the effect of the EE of C. sylvestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
1
8
0
4
Order By: Relevance
“…They found that this activity was higher than butylated hydroxytoluene (BHT) and quercetins in lower concentrations by the phytochemical composition of phenolic compounds (flavonoids and coumarins). The authors described the improvement of lipidic profile in vivo with ethanolic extract, corroborating previous antihyperlipidemic activity, 39 and possible cardioprotective effects associated with lipid profile enhancement 38 . Vieira‐Júnior et al .…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…They found that this activity was higher than butylated hydroxytoluene (BHT) and quercetins in lower concentrations by the phytochemical composition of phenolic compounds (flavonoids and coumarins). The authors described the improvement of lipidic profile in vivo with ethanolic extract, corroborating previous antihyperlipidemic activity, 39 and possible cardioprotective effects associated with lipid profile enhancement 38 . Vieira‐Júnior et al .…”
Section: Resultssupporting
confidence: 72%
“…The activity of C. sylvestris methanolic extract was more significant in PND preparations incubated with venom or toxin and was possibly associated with the phytocomplex of glycosylated flavonoids containing rutin in the majority; nevertheless, rutin alone did not show the same effect 34,36 . Espinosa et al 38 . evaluated the antioxidant activity of ethanolic extract of C. sylvestris in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations in vitro and in vivo have already pointed out the anti-inflammatory action of different preparations of C. sylvestris (alcoholic/aqueous extracts or essential oils), and they have demonstrated inhibition of edema activity, leukocyte migration, myeloperoxidase activity, nitrogen-derived free radical compounds [22][23][24]26,27,[54][55][56], phospholipase A2, and tissue proteases [81]. Certainly, the involvement of inflammatory mediators, such as prostaglandins, leukotrienes, cytokines, and biogenic amines, activates and sensibilizes C fiber-related polymodal nociceptors, which play an important role in cutaneous hyperalgesia triggered by mechanical and/or thermal stimuli [15].…”
Section: Analgesic In Vivo Effectsmentioning
confidence: 99%
“…Among them, Casearia (Salicaceae) comprises about 180 species distributed in sub-tropical and tropical regions [16] and has promising anticancer effects [17][18][19]. In Brazil, Casearia sylvestris Sw. is the most known species and has shown antifungal [20], anxiolytic [21], antibacterial [22], antioxidant [23,24], antileishmanial [25], anti-inflammatory [26,27], and antimicrobial [24,28] activities.…”
Section: Introductionmentioning
confidence: 99%